Performance study on yield and yield attributes of seven white jute breeding lines at different regions of Bangladesh - Miah, A; Saha, NR; Rafiq, MZA; Ali, MY; Hasanuzzaman, M (Progressive Agriculture, 2020)
The study was conducted to know the performance of growth, yield contributing parameters and yield of seven white Jute breeding line and two checks (CVL-1 and CVE-3) at five different jute research regional stations of Bangladesh Jute Research Institute (BJRI) during the period from March to September 2014. The experimental data was laid out in a completely randomized block design with three replications and the means were adjudged by DMRT at 5% level of probability. The performances of experimental lines were showed statistically significant variation among the studied whole growth, yield and yield attributing traits. Analysis of variance revealed significant differences among the treatments for fibre yield and stick yield at Rangpur plant height, base diameter, fibre and stick yield at Manikganj plant height and fibre weight at Chandina, Faridpur and plant height at Kishoreganj. It was revealed by the pooled mean performance that among the genotypes, the line C-5018 m produce the tallest plant among the lines. The Line C-5030 recorded both the highest plant population (0.241 m/ha) and base diameter (21.79 mm). The line C-5133 showed highest Green weight with leaves (43.12 t/ha) whereas C-5149 recorded the greatest Green weight without leaves (35.02 t/ha). The most important parameter is the fiber yield and the highest-fibre weight (2.83 t/ha) was recorded by the line C-5149 among the seven breeding line. The line C-5149 also recorded the highest amount of stick yield (6.01 t/ha). However, pooled mean over stations revealed that no progenies, C-5018, C-5030, C-5036, C-5044, C-5133, C-5136, C-5149 out-yielded both the check varieties CVL-1 (2.83 t/ha) and CVE-3 (2.54t/ha) whereas C-5149(2.83t/ha) shows the equivalent result as CVL-1. It was also revealed that C-5030(2.61t/ha), C-5136(2.70t/ha) and C-5149(2.83t/ha) out yielded check variety CVE-3 (2.54t/ha). Progressive Agriculture 31 (1): 19-25, 2020